GE_GERICHTE P/2141/2011 vom 28. April 2012 - GE Cour de justice (2012)
DISPOSITIONS PÉNALES DE LA LCR ; DROIT D'ÊTRE ENTENDU ; ACTE D'ACCUSATION | LCR.91a.1; LCR.51.3; CPP.9.1; Cst.29.2; CPP.325.1; CPP.350.1; CPP.333.1